Informality of actors and its implications for Potato Value Chain upgrading in Uganda - Mwesigye, Francis; Mbowa, Swaibu (Economic Policy Research Centre, 2016)
This brief summarizes the findings of the potato value chain study on the following factors; level of informality, size of operation and the length of relationships between the processors, traders and other value chain players1. The study reveals that most potato value chain actors operate on a very small scale and are informal- not registered and unlicensed. For instance, 70% of the interviewed agro-input dealers are small scale retailers and about 60% of agro-input dealers are not registered. Also, only 3% of traders are registered and 13% have trade licenses. Whereas 67% of processors have trade licenses, only 13% are registered. These findings suggest that there is a high level of informality in the sector. Business informality is costly to the government and to the public in terms of lost tax revenue and health and safety risk due to non-regulation and non-standardization. In addition, the high level of informality constrain value chain actors from obtaining formal credit and other sources for funding as they are not legal entities. Informality stems from cumbersome procedures and high cost of registering a busness2. On the other hand, some busness owners prefer to operate informally so as to evade taxes. Therefore, to enhance registration, the government should shorted the process and reduce the cost.